2015
DOI: 10.1080/07373937.2015.1010208
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Microencapsulation with Freeze Pretreatment: Spray-Dried Oil in Water Emulsion Stabilized by the Soy Protein Isolate–Gum Acacia Complex

Abstract: Spray-dried microparticles with lipid cores that dissolve β-carotene were prepared using a technique based on the complexation of soy protein and gum acacia. A freeze-pretreatment was applied to modify the resultant properties of the dried particles.An o/w emulsion stabilized by soy protein isolate was mixed with gum acacia. The pH of the solution was adjusted to a selected value; this solution was frozen and thawed under controlled thermal protocols, and spray-dried to obtain the final products. Complexation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The nature of the emulsifier used to coat the oil droplets in an emulsion or nanoemulsion also plays a critical role in determining the physicochemical properties of the powders produced after dehydration. Previous studies have reported that β-carotene-loaded oil droplets stabilized by various kinds of emulsifiers can be converted into powders, including gum arabic (Lim, Burdikova, Sheehan, & Roos, 2016), almond gum (Mahfoudhi & Hamdi, 2014), modified starch (Liang, Huang, Ma, Shoemaker, & Zhong, 2013), hydroxypropyl cellulose (Claudia P. Coronel-Aguilera & San Martín-González, 2015), sodium caseinate (C. P. Coronel-Aguilera & Martin-Gonzalez, 2015), soy protein (Deng, Chen, Huang, Fu, & Tang, 2014), soy protein-gum arabic complex (Nakagawa & Fujii, 2015), and cyclodextrin (Durante, Lenucci, Marrese, Rizzi, De Caroli, Piro, et al, 2016). Most of these studies used spray dry to prepare nanoemulsion powder and were aimed to determine the physiochemical properties of dried powder, or to increase carotenoid stability by manipulating the composition.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the emulsifier used to coat the oil droplets in an emulsion or nanoemulsion also plays a critical role in determining the physicochemical properties of the powders produced after dehydration. Previous studies have reported that β-carotene-loaded oil droplets stabilized by various kinds of emulsifiers can be converted into powders, including gum arabic (Lim, Burdikova, Sheehan, & Roos, 2016), almond gum (Mahfoudhi & Hamdi, 2014), modified starch (Liang, Huang, Ma, Shoemaker, & Zhong, 2013), hydroxypropyl cellulose (Claudia P. Coronel-Aguilera & San Martín-González, 2015), sodium caseinate (C. P. Coronel-Aguilera & Martin-Gonzalez, 2015), soy protein (Deng, Chen, Huang, Fu, & Tang, 2014), soy protein-gum arabic complex (Nakagawa & Fujii, 2015), and cyclodextrin (Durante, Lenucci, Marrese, Rizzi, De Caroli, Piro, et al, 2016). Most of these studies used spray dry to prepare nanoemulsion powder and were aimed to determine the physiochemical properties of dried powder, or to increase carotenoid stability by manipulating the composition.…”
Section: Introductionmentioning
confidence: 99%
“…The best yield and EE was achieved with milk proteins instead of proteins obtained from tissues. Likewise, several researchers have evaluated the encapsulation activity of proteins such as gelatin [19,45,51], sodium caseinate in combination with lactose, or maltodextrin and other proteincarbohydrate complexes [19]. Remarkably, Rubio and his team [52] patented the process to obtain microcapsules and nanocapsules based on free whey proteins or complex poly saccharides employing "Blow-spinning," "blow-spraying," "electrospinning" and "electro spraying" as encapsulation techniques.…”
Section: Proteins Used As Coating Materials: An Emergent Trendmentioning
confidence: 99%
“…Microencapsulation by spray drying is the most widely known technique used to encapsu late food ingredients such as vitamins (C and E), fragrances, probiotic bacteria, lipids, veg etable oils, minerals (i.e., iron), anthocyanin pigments, milk, and foodstuffs [45,47,48,60,69]. The technique of microencapsulation by spray drying has been used since the 1950s and is currently applied at the industrial and academic level due to its rapid speed, economy and sim plicity.…”
Section: Spray Dryingmentioning
confidence: 99%
See 2 more Smart Citations